Whiskey in a teacup : what growing up in the South taught me about life, love, and baking biscuits - Witherspoon, Reese, 1976- (Touchstone, 2018)
The award-winning actress reflects on her Southern heritage and how it is infused into every part of her life, and shares some of her grandmother Dorothea's favorite recipes and traditions.